2020
DOI: 10.21203/rs.3.rs-16784/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

FNDC5/Irisin improves the therapeutic efficacy of bone marrow-derived mesenchymal stem cells for myocardial infarction

Abstract: Background: The beneficial functions of bone marrow mesenchymal stem cells (BM-MSCs) decline with decreased cells survival, limiting their therapeutic efficacy for myocardial infarction (MI). Irisin, a novel myokine which is cleaved from its precursor fibronectin type III domain-containing protein 5 (FNDC5), is believed involved in a cardioprotective effect but little was known on injured BM-MSCs and MI repair yet. Here, we investigated whether FNDC5 or irisin could improve the low viability of transplanted BM… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 37 publications
2
9
0
Order By: Relevance
“…Future work is required to determine the molecular and cellular mechanisms underlying the catch-up and facilitation, which were well correlated with IL-35 promotion of macrophage survival and improvement of wound healing after myocardial infarction ( 85 ). In addition, differences between the IL-35 roles in angiogenesis in HLI and myocardial infarction may also result from potential functions of cardiokines ( 86 ) and myokines ( 87 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future work is required to determine the molecular and cellular mechanisms underlying the catch-up and facilitation, which were well correlated with IL-35 promotion of macrophage survival and improvement of wound healing after myocardial infarction ( 85 ). In addition, differences between the IL-35 roles in angiogenesis in HLI and myocardial infarction may also result from potential functions of cardiokines ( 86 ) and myokines ( 87 ).…”
Section: Discussionmentioning
confidence: 99%
“…Of note, the stronger protection of IL-35 in the cardiac muscle than in the skeletal muscle may be due to tissue specificity. In addition, differences between the IL-35 roles in angiogenesis in HLI and myocardial infarction may also result from potential functions of cardiokines ( 86 ) and myokines ( 87 ). These findings provide a novel insight on the future therapeutic potential of IL-35 in suppressing ischemia/inflammation-triggered inflammatory angiogenesis at the early phase but sparing regenerative angiogenesis at the late phase, which is similar to our recent report that IL-35 inhibits human aortic endothelial cell activation triggered by proatherogenic lipids but spare trained immunity pathway ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Bone marrow MSCs derived conditioned medium could prevent aneurysm growth through macrophage polarization regulation (Zhou et al, 2019). In addition, precursor fibronectin type III domain-containing protein 5 or irisin, a novel myokine has the potential to improve bone marrow MSC mediated paracrine effect and engraftments in infarcted hearts (Deng et al, 2020). Previous studies have shown that MSC-derived exosomes have distinct properties, including immunomodulation, angiogenesis, and paracrine effect that protect organ functions in animal studies.…”
Section: Angiotensin II In Stem Cell Therapy In Cardiovascular Systemmentioning
confidence: 99%
“…Apart from this, its expression and role in various other conditions such as in ammation, cardiovascular diseases, aging and other metabolic conditions have been reported [18][19][20]. In addition, our previous study showed that FNDC5 pre-treatment BMMSCs improved MI repair [21]. Interestingly, we also found that BMMSCs with overexpression of FNDC5 secreted more exosomes compared ordinary BMMSCs.…”
Section: Introductionmentioning
confidence: 57%